The influence of learning facilities, learning motivation, and learning satisfaction on students’ learning interests - Muhammad Harli Hanapi; Hizkia Manurung; Mayshel Adinda Viola (Institute of Information Technology and Social Science (IITSS), 2024)
The study examines how students' interest in learning is affected by learning motivation, learning satisfaction, and learning engagement. Quantitative methodology that relies on basic random sampling techniques to compile data. This study included 177 participants from 8 different institutions in Jambi City. The study found that students' academic progress and enjoyment are significantly affected by learning facilities, learning motivation, and excitement in learning. Reliability and construct validity testing were carried out using the Fornell-Larcker, Cross-loading, and HTMT analysis methods, showing good discriminant validity. The structural model tested supports a positive relationship between exogenous and endogenous constructs, as well as all proposed hypotheses. This study used the PLS-SEM (partial least squares plus structural equation modeling) approach. Although students' interest in learning is influenced by learning motivation, the study found that having a suitable learning approach. Although students' interest in learning is influenced by learning motivation, the study found that having suitable learning facilities had a positive effect on students' motivation and satisfaction with learning. Using a 5-point Likert scale, construct behavior analysis was carried out, resulting in high average variable effect values. Implications for future study highlight the need to enhance learning facilities, learning motivation, and student learning satisfaction as means to successfully raise interest in learning within the framework of higher education. In order to increase students' interest and motivation in studying, it is essential to provide them with a helpful learning environment.